2019
DOI: 10.2106/jbjs.19.00438
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Reference Axes for Femoral Component Rotation in Total Knee Arthroplasty

Abstract: Background: Many reference axes are used to evaluate rotation of the femoral component during total knee arthroplasty, including the Whiteside line, surgical transepicondylar axis (sTEA), anatomical transepicondylar axis (aTEA), posterior condylar axis externally rotated 3° (PCA+3°ER), sulcus line, and femoral transverse axis (FTA). There is no consensus about which of these axes is most accurate. Methods: The Stryker Orthopaedic Modeling and Analytics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…This significant difference was also found in comparison with 3D-CT measurements (− 4.92 ± 2.92 for Kanekasu; − 4.04 ± 1.95 for 2D-CT), which are based on the aTEA. These findings are in keeping with accepted principles [ 16 , 26 , 29 , 30 ]. A recent study of Jang et al [ 29 ] evaluated various reference axes of the femur based on 2128 CT scans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This significant difference was also found in comparison with 3D-CT measurements (− 4.92 ± 2.92 for Kanekasu; − 4.04 ± 1.95 for 2D-CT), which are based on the aTEA. These findings are in keeping with accepted principles [ 16 , 26 , 29 , 30 ]. A recent study of Jang et al [ 29 ] evaluated various reference axes of the femur based on 2128 CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in keeping with accepted principles [ 16 , 26 , 29 , 30 ]. A recent study of Jang et al [ 29 ] evaluated various reference axes of the femur based on 2128 CT scans. They found that the aTEA differed from the sTEA by a mean of 2.05° ± 1.33°.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the MedL/LatL did not statistically differ between the sTEA and WSL in the entire study population and male subjects alone; nonetheless, there was a difference between the sTEA and WSL in female subjects. Jang et al reported an average difference of 1.9° between the WSL and sTEA, regardless of ethnicity or sex [ 34 ], and Reddy et al reported that there was no statistical difference between Indian men and women when using either the WSL or sTEA [ 35 ]. Koh et al reported no statistical difference in the groove angle of the proximal trochlea between men and women in a Korean study [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rotational malalignment of the femoral component in TKA is associated with poor outcomes, including flexion instability, patellar maltracking, premature wear of the polyethylene, stiffness, anterior knee pain, and patient dissatisfaction. [ 13 , 14 ] During TKA, the rotation alignment and installation position of the femoral component are generally based on the anatomical signs of the distal femur. The most widely used anatomical signs are the APA, STEA, and PCL.…”
Section: Discussionmentioning
confidence: 99%